Analyzing the Measurement of Employee Performance using Human Resources Scorecard Method and Analytical Hierarchy Process - Baheshti, Ahmad; Safirin, Mochamad Tutuk (Journal La Multiapp, 2024)
PT. XYZ is a marine cargo expedition company engaged in cargo transportation services, shipping and sea distributors. This study aims to measure employee performance of PT. XYZ using Human Resources Scorecard (HRSC) method where the measurement system is based on 4 perspectives which include financial, customer, internal business process, and learning and growth perspective. The weighting method using the Analytical Hierarchy Process (AHP). The results can be concluded that the financial perspective performance is 3.62, the customer perspective performance is 4, the internal business process perspective performance is 4, and the learning and growth perspective performance is 3.87. Comprehensively, human resource performance is 3.78 (high). This indicates that comprehensive employee performance is good, but some improvements are needed so that employee performance can increase.